Assistência coletiva em mulheres obesas mórbidas em um Hospital Universitário: análise de um ano - Santos, Jessica Menin Néia dos (2024)
Obesity is considered a chronic condition, characterized by the excessive accumulation of adipose tissue, involved in several complications and comorbidities. Due to the alarming increase in its prevalence, it is considered a global epidemic. To monitor this condition, the collective modality has been gaining ground, as the exchange of experiences proves to be essential for adherence to treatment. To evaluate the impact of one year of collective assistance on the biochemical and athropometric markers of morbidly obese women attended to in a highly complex hospital service. Anthropometric data such as BMI, total body H2O, lean tissue (%), body fat (%), adipose tissue mass (kg) and biochemical markers such as complete blood count, lipid profile, renal and hepatic function, vitamins, and minerals of 18 female participants aged ≥ to 18 years undergoing clinical treatment for obesity in preparation for bariatric surgery were analyzed. For statistical analysis, p<0.05. Sample including female patients, with an average age of 42,6 years, married or in a stable union, low education level, between primary and incomplete secondary education, average family income of R$2278,00. There was an increase in total cholesterol (p = 0.0151) and LDL (p = 0.0396) and a reduction in the values of Vitamin D and Calcium (p = 0.0099; p=< 0.0001 respectively); Reduction in BMI (p = 0.046), but decrease in total body water (p= <0.0001), reduction in lean tissue % (p=0.0001) and increase in total body fat mass (63,7% versus 59,9% at the beginning of follow up). Our collective study demonstrated a reduction in mean BMI, with a reduction in total body water volume, lean tissue %, total fat % and adipose tissue mass (kg). Regarding biochemical markers, there was a reduction in vitamin D and calcium, and an increase in total and LDL cholesterol. Limiting factors must be taken into account, such as the sample number and the fact that some biochemical tests were not performed on the entire sample.